POLA PENGGUNAAN DAN KERASIONALAN OBAT TERHADAP LAMA RAWATAN PADA PASIEN MALARIA DI RSUD DR. M. YUNUS BENGKULU - Versita, Riana; Almasdy, Dedy; Dahlan, Zaini (JURNAL MEDIA KESEHATAN, 2021)
This study was aimed to describe the relationship of drug uses rasionality, disease severity and pattern of drug uses on Malaria at Dr. M. Yunus Bengkulu Hospital. This was in observasional study with cross-sectional using datas of medical record. The result showed 101 of patient datas filled up eligibility criteria as inclusion and exclusion, 23 of them changed diagnosis and 78 datas did not changed diagnosis. Demographic and clinical characteristic test, evaluation of rationality used Gyssen and Drug Related Problem (DRP) and relations between variable used Chi-square and Independent T-Test gave 95% of confidence interval. Relation of socio-demographic characteristic in group of age was 4.314 times impacted than gender and education on changing diagnosis. where moderate severity has longer duration of treatment than mild severity, while in cost of treatment was not significantly (p>0.05). In pattern of drug, single and combination was not significantly (p>0.05) on duration of treatment , in statistically, single drug uses was more effective but should be researched about relapse incidence on malaria patient which use single drug. Rationality of drug relations against duration of treatment was significantly (p<0.05), rational drug has shorter duration than irrational drug of treatment, so more effective and efficient. This study also showed DRP with improper drug selection was 34.26%.